Prophetic preaching in a post-apartheid South Africa : an URCSA perspective - Mahokoto, Marlene S. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MDiv (Practical Theology and Missiology))--Stellenbosch University, 2007.